Development of inhibition and switching: A longitudinal study of the maturation of interference suppression and reversal processes during childhood. (November 2018) - Richardson, Cassandra; Anderson, Mike; Reid, Corinne L.; Fox, Allison M.
Abstract: Inhibition and switching are executive functions (EFs) that have different developmental trajectories across childhood. The development of specific processes unique to each EF may contribute to these trajectories. Interference suppression and reversal were examined in a large sample of children aged 7 and 9 years (n = 120) and followed-up after two-years to investigate developmental trajectories of inhibition and switching. The N2 and P3b components provided neural correlates of conflict monitoring and attentional processing of conflict involved in interference suppression and reversal. Interference suppression improved over time, however, switching performance did not significantly change between 7 and 11 years. Improvements in correct RT with age and time indicated increased efficiency of stimulus evaluation, response preparation and execution. N2 amplitude decreased with both age and time, indicating less reliance on conflict monitoring to signal cognitive control to manage stimulus and response conflict. P3b amplitude modulations indicated that different amounts of attention were allocated to updating mental representations of interference suppression and reversal task features. These data indicated different developmental trajectories of specific processes unique to inhibition and switching across the childhood period of 7–11 years, providing further empirical evidence that 7–11 years is a critical period for cognitive development.